Affect and reason in divided societies: entanglement, conflict, possibility. Issue 3 (2nd September 2021) - Tønder, Lars
ABSTRACT: This essay introduces the special issue on affect and reason in deeply divided societies. Common to all essays in the special issue is a shared belief that political and social theory need a new framework for analyzing the relationship between affect and reason. This goes especially for societies marked by ever-growing cleavages, ethnic diversity, ideological struggles, and deep political pluralism. The purpose of this introductory essay is to outline – and substantiate – the reasons behind this belief. The essay provides an overview of the current debate on affect and reason, highlighting both contributions and limitations. The essay then proceeds to outline the specifics of the alternative framework developed in the ensuing 10 essays.